Security of the development of the construction industry in conditions of macroeconomic market uncertainty - Krupnik Dorota; Stryjewski Tomasz (2023)
The economic situation in Poland at the beginning of 2020 was marked by the expected and forecast economic slowdown. In the conditions of uncertainty in the functioning of the organization in the first half of 2020, factors that allowed for increasing the stability and security of production processes and minimizing risk, especially in relation to supply chains, played an important role. The aim of the article is to identify and analyze problems related to the safe functioning of construction industry organizations in conditions of market uncertainty. The following research problem was posed in the work: what econometric determinants can influence demand and inflation processes in market conditions? While conducting the research, the following hypothesis was formulated and verified: construction is an indicator of mechanisms and factors stimulating the development and restrictions on the market in the last few years, which may teach the need to select appropriate macroeconomic and management tools on a global scale to manage one's own organization. The research used statistical methods, comparative analysis, index analysis, ECM model, direct observation of production processes and company activities. The proposed model has been verified and empirically tested in market conditions. The presented material is the result of empirical research in the construction industry operating on the global market as a capital group, including in Poland. The issues examined included, among others: elements such as: analysis of the investment market, unemployment rates, factors influencing the economic situation, analysis of GDP determinants in Poland, inflation processes affecting the stability of the construction industry, including its logistics processes. Without the ability to research market trends, analyze development directions, factors determining development or stagnation, it is not possible to achieve success in the construction industry.